Implementation of the Picture and Picture Learning Model in Science Learning for Grade V Students - Agustina, Triya; Hamdan, Hamdan; Egok, Asep Sukenda (Civiliza Publishing, Indonesia., 2025)
Learning activities are the process of interaction between students, educators, and learning resources in the learning environment. This study aims to determine the completeness of the learning outcomes of Natural and Social Sciences (IPAS) of fifth-grade students of SD Negeri 1 Sumber Harta after being given the Picture and Picture learning model. The background of this study is the low learning outcomes of students in the subject of IPAS caused by the use of monotonous learning methods and less involvement of student activity. This study uses a quantitative approach with a quasi-experimental method and a one-group pre-test and post-test design. The subjects of the study were all 18 fifth-grade students. The data collection technique used a written test in the form of essay questions. The results showed that the average pre-test score of 37.35 increased to 78.38 in the post-test, with the learning completeness level increasing from 11.11% to 88.89%. Statistical tests using the z-test show that the calculated z value is 4.97, which is greater than the z (table) of 1.64 at a significance level of 0.05, which means the alternative hypothesis is accepted. Thus, it can be concluded that the application of the picture and picture learning model can significantly improve students' science learning outcomes.